Incidence and predictors of venous thromboembolism recurrence after a first isolated distal deep vein thrombosis. (April 2014) - Galanaud, J.‐P.; Sevestre, M.‐A.; Genty, C.; Kahn, S. R.; Pernod, G.; Rolland, C.; Diard, A.; Dupas, S.; Jurus, C.; Diamand, J.‐M.; Quere, I.; Bosson, J.‐L.; et al.
Summary Background Isolated distal deep vein thrombosis (iDDVT) (i.e. without proximal DVT or pulmonary embolism) represents half of all cases of lower limb DVT. Its clinical significance and management are controversial. Data on long‐term follow‐up are scarce, especially concerning risk and predictors of venous thromboembolism (VTE) recurrence. Methods Using data from the OPTIMEV (OPTimisation de l'Interrogatoire dans l'évaluation du risque throMbo‐Embolique Veineux) study, a prospective, observational, multicenter study, we compared, 3 years after an index VTE event and after discontinuation of anticoagulants, (i) the incidence and type of recurrence in patients without cancer with a first iDDVT vs. a first isolated proximal DVT (iPDVT) and (ii) predictors of recurrence after iDDVT. Results Compared with patients with iPDVT (n = 259), patients with an iDDVT (n = 490) had a lower annualized incidence of overall VTE recurrence (5.2% [95% confidence interval 3.6–7.6] vs. 2.7% [1.9–3.8], respectively; P = 0.02) but a similar incidence of pulmonary embolism recurrence (1.0% [0.5–2.3] vs. 0.9% [0.5–1.6], respectively; P = 0.83). An age of > 50 years, unprovoked character of index iDDVT, and involvement of more than one vein in one or both legs each independently tripled the risk of recurrence, with the latter then being ≥ 3% per patient‐year. Neither muscular vein nor deep‐calf vein location of iDDVT nor clot diameter with compression influenced the risk of recurrence. Conclusions After stopping anticoagulants, patients with iDDVT have a significantly lower risk of overall VTE recurrence than did patients with iPDVT but a similar risk of serious recurrent VTE. Age > 50 years, unprovoked iDDVT, and number of thrombosed veins (more than one) influenced the risk of recurrence and may help to define patients at significant risk of recurrence.